Midline versus paramedian mandibulotomy for tongue cancer surgery: analysis of complications. Issue 6 (June 2022) - Chiu, T.-H.; Marchi, F.; Huang, S.-F.; Kang, C.-J.; Liao, C.-T.; Hung, S.-Y.; Cheong, D.C.-F.; Tsao, C.-K.
Abstract: Midline and paramedian mandibulotomies both have distinct anatomical and surgical strengths. A retrospective study was performed at Chang Gung Memorial Hospital, Linkou Branch between 2014 and 2019 to investigate how the osteotomy site (midline ( n = 221) or paramedian ( n = 44)) and type (straight, notched, or stair-stepped) affect postoperative and post-radiotherapy complications in patients undergoing wide excision of tongue cancer with flap reconstruction. Midline mandibulotomies were predominantly of the straight osteotomy type, while paramedian mandibulotomies were mostly notched type ( P < 0.001). Comparably low elective tooth extraction rates were found in both approaches ( P = 0.556). Paramedian mandibulotomy showed a higher osteoradionecrosis rate ( P = 0.026), but there was no significance in the sub-analysis of individual types. Paramedian sites were associated with more early infection ( P = 0.036) and plate exposure ( P = 0.036) than midline sites with the straight osteotomy type, but complication rates did not differ significantly for the notched and stair-stepped types. Paramedian sites ( P = 0.020) and notched types ( P = 0.006) were associated with higher odds of osteoradionecrosis in the univariable logistic regression analysis, but only the notched type remained significant in the multivariable analysis ( P = 0.048). In conclusion, paramedian sites increased the rate of osteoradionecrosis, and correlation with the osteotomy type resulted in more osteoradionecrosis in notched types and more complications in straight paramedian mandibulotomies.